Effect of aging on the mechanical behavior of aluminum-steel composites processed by accumulative roll bonding. (2021) - Tahir, Furqan; Yapici, Guney Guven
Abstract: Severe plastic deformation (SPD) processes have been widely used to provide ultrafine-grained (UFG) structures along with enriched strength in various metals. This study focuses on accumulative roll bonding (ARB), an SPD method, which was employed to fabricate aluminum and interstitial free steel composite, while the effect of heat-treatment was investigated by the resulting mechanical behavior. Improvement in strength and ductility levels was attained with increasing aging time, indicating the formation of precipitates among aluminum layers. Substantial enhancements in tensile strength and elongation of 420 MPa and 18%, respectively were exhibited after 24hr aging time. Interface strength raised consistently throughout the aging treatments which was about 270 MPa under shear.